Transferrin and Prealbumin Identify Esophageal Cancer Patients with Malnutrition and Poor Prognosis in Patients with Normal Albuminemia: A Cohort Study. (26th November 2022) - Chiang, Hsueh-Chien; Lin, Meng-Ying; Lin, Forn-Chia; Chiang, Nai-Jung; Wang, Yi-Ching; Lai, Wu-Wei; Chang, Wei-Lun; Sheu, Bor-Shyang
Abstract: In this study, we aimed to analyze whether serum prealbumin and transferrin have a higher sensitivity than albumin for detecting malnutrition and predicting survival in esophageal cancer patients. A total of 212 patients were prospectively enrolled. Serum albumin, prealbumin, and transferrin were analyzed by enzyme-linked immunosorbent assays. The association of nutritional markers with survival was analyzed. We found that malnutrition was presented in 44.5% of the patients, while 56.6% were unaware of their body weight change. The area under the curve for diagnosing malnutrition was largest for prealbumin, followed by transferrin and albumin, with optimal breakpoints of 21 mg/dL, 206 mg/dL, and 4.3 g/dL, respectively, for diagnosing malnutrition. The diagnostic sensitivity for malnutrition was 34.1-63.4% with a single marker and this increased to 80.5% with all 3 markers. In patients with normal albuminemia (≥ 4.3 g/dL), a low level of prealbumin and/or transferrin predicted malnutrition and poor prognosis. Multivariate Cox regression analysis confirmed that a low level of the nutritional marker was an independent poor prognostic factor. In conclusion, serum prealbumin and transferrin outperformed albumin in identifying esophageal cancer patients with malnutrition and poor prognosis. Checking all three markers will help with the early diagnosis of malnutrition and enable timely intervention.